Investigation of possibilities for astronomical meridian determination by the hour angle of the Sun - Petroškevičius, Petras; Obuchovski, Romuald (Geodesy and Cartography, 2012)
Results of investigation of the astronomical meridian determination possibilities are presented in the paper. For defining the meridian direction the method of astronomical azimuth determination by the hour angle of the Sun is analysed. Best conditions for the Sun’s azimuth determination were investigated. Effect of points and the Sun’s coordinate errors were analysed. Relation of hour angle of the Sun error effect on the Sun declination and latitude was determined. Possibilities for the latitude and declination errors effect reduction are specified. Special features for horizontal angle between selected direction and the Sun observation are analysed. Effect of the Sun’s visual radius and azimuth change acceleration was analysed. Based on the obtained results, it is possible to select an optimal time for determining the astronomical azimuth of direction as well as for determining the direction of astronomical meridian, depending on known parameters errors, point latitude and season.Article in Lithuanian.Astronominio dienovidinio nustatymo pagal Saulės valandinį kampą galimybių tyrimasSantrauka. Pateikiami astronominio dienovidinio nustatymo galimybių tyrimo rezultatai. Dienovidinio krypčiai gauti nagrinėjamas astronominio azimuto nustatymo pagal Saulės valandinį kampą metodas. Ištirtos geriausios Saulės azimuto nustatymo sąlygos. Išnagrinėta punkto ir Saulės koordinačių paklaidų įtaka. Nustatyta Saulės valandinio kampo paklaidos įtakos priklausomybė nuo Saulės deklinacijos ir platumos. Nurodytos platumos ir deklinacijos paklaidų įtakos mažinimo galimybės. Išnagrinėti horizontaliojo kampo tarp pasirinktos krypties ir Saulės matavimo ypatumai. Išanalizuota Saulės regimojo spindulio ir azimuto kitimo pagreičio pokyčių įtaka. Remiantis gautais tyrimų rezultatais galima pasirinkti tinkamiausią laiką krypties astronominiam azimutui, o kartu ir astronominio dienovidinio krypčiai nustatyti, atsižvelgiant į žinomas parametrų paklaidas, punkto platumą ir metų laiką.Prasminiai žodžiai: astronominis dienovidinis, astronominis azimutas, geriausios sąlygos Saulės azimutui nustatyti, astronominio azimuto nustatymas pagal Saulės valandinį kampą.First published online: 03 Aug 2012